2022
DOI: 10.1039/d2dt03078k
|View full text |Cite
|
Sign up to set email alerts
|

Dual mode of voltammetric studies on Cu(ii) complexes of His2 peptides: phosphate and peptide sequence recognition

Abstract: Copper(II) complexes of peptides with a histidine residue at the second position (His2 peptides) provide a unique profile of electrochemical behavior, offering signals of both Cu(II) reduction and Cu(II) oxidation....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Then, we used a voltammetric chemical tongue to identify peptides within the group of Pro-Gly, carnosine, glutathione, Aβ 4-16 , and the α-factor N-terminus [ 20 ]. In our last paper, we showed that voltammetric tongue approach enabled recognition of sequence of Aβ 5-9 derivatives, which presents the same Cu(II)-His2 coordination mode, but with modified residues at first and third positions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, we used a voltammetric chemical tongue to identify peptides within the group of Pro-Gly, carnosine, glutathione, Aβ 4-16 , and the α-factor N-terminus [ 20 ]. In our last paper, we showed that voltammetric tongue approach enabled recognition of sequence of Aβ 5-9 derivatives, which presents the same Cu(II)-His2 coordination mode, but with modified residues at first and third positions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%